Additive‐Free Ultrastable Hydrated Vanadium Oxide Sol/Carbon Nanotube Ink for Durable and High‐Power Aqueous Zinc‐Ion Battery. Issue 15 (7th April 2022) - Jin, Hongrun; Li, Fen; Gao, Jiasong; Liu, Kaisi; Luo, Yongxin; Zhou, He; Yao, Bin; Duan, Jiangjiang; Hu, Bin; Huang, Liang; Zhou, Jun
Abstract: Aqueous zinc‐ion batteries (ZIBs) based on near‐neutral electrolytes represent a promising large‐scale energy storage solution for a deeper and broader penetration of clean renewable energy. The preparation of electrode paste is vital for the normal performance and stability of ZIBs. Herein, the authors report an additive‐free V2 O5 ·1.6H2 O ( h ‐V2 O5 )/carbon nanotube (CNT) hybrid ink to prepare large‐scale free‐standing h ‐V2 O5 /CNT film for high‐rate and durable ZIBs. The as‐prepared h ‐V2 O5 /CNT film exhibits a high specific capacity of 446.4 mA h g −1 (volumetric capacity of 839.2 mA h cm −3 ) at 0.2 A g −1 when used as cathode for ZIBs. It retains considerable capacities of 202.3 and 139.0 mA h g −1 even at high current densities of 20 and 50 A g− 1, respectively, exhibiting ultrahigh rate capability. The assembled cell also displays outstanding long‐term cycling stability with a remarkable capacity of 309.7 mA h g −1 even after 3500 cycles at 10 A g −1 . More importantly, this h ‐V2 O5 sol can serve as a general "surfactant" to disperse a variety of nanomaterials in water. This work proposes a facile strategy to prepare additive‐free paste for conductive electrode, which holds great potential for a broad range of applications. Abstract : An additive‐free h ‐V2 O5 /carbon nanotube (CNT) ink is developed by using V2 O5 ·1.6H2 O sol as "surfactant", which is universal and highly processable and can be applied to a broad‐array of electrode fabrication techniques. The as‐prepared h ‐V2 O5 /CNT cathode delivers excellent rate capability and a long‐term cycling stability in zinc‐ion batteries, holding a huge potential in high‐performance electrochemical energy storage devices.